A Partial Least Squares Structural Equation Modeling Analysis of Early Fertility, Knowledge and Behaviors among Indigenous Young Women in Guatemala (European Journal of Behavioral Sciences, 2023)
Despite that Guatemala has health inequality among non-indigenous and indigenous women, adolescent fertility has been scarcely studied. This study investigates the mechanism of early fertility among indigenous women aged 20-29 using data from the Guatemalan Demographic Health Survey 2014–2015 (N=8,110). Partial least squares structural equation modeling analysis (PLS-SEM) were conducted in among indigenous women in urban area (UI) or rural area (RI) and non-indigenous women in rural area (RN) to examine the associations between socioeconomic variables, mediators (knowledge and attitudes toward early pregnancy prevention) and an outcome (early fertility). Results showed that geographical difference had stronger influence than ethnicity. Early fertility in RI is influenced by more factors than UI and RI, such as media exposure, attitudes and knowledge on pregnancy prevention, contraceptive use, in addition to education and risky sexual behaviors. Having better knowledge on contraceptive methods did not reduce risky sexual behaviors. Further discussion on elaboration of variables measuring the actual decision-making related to risky sexual behaviors are suggested.